Analisis Kelayakan Ekowisata Hungayono Sebagai Destinasi Wisata Berbasis Konservasi Di Taman Nasional Bogani Nani Wartabone - Nurfitra, Khalifah; Epa, Ni Luh; Suudi, Nur Rahmatiya H.; Tahaku, Dhea Ananda Pratiwi (Jurnal Kajian Pariwisata Dan Perhotelan, 2025)
his research aims to analyze the feasibility of the Hungayono area within Bogani Nani Wartabone National Park (TNBNW) as a conservation-based ecotourism destination. TNBNW is the largest land conservation area in Sulawesi, which has a wealth of biodiversity and is an important habitat for endemic species such as Maleo birds (Macrocephalon maleo). The study was conducted using a descriptive qualitative approach based on secondary data obtained through documentation and literature studies. Feasibility assessment was conducted on five main aspects: tourism attraction, accessibility, facilities, community and environmental conditions, as well as management and services. The results showed that the Hungayono area obtained a feasibility index value of 69%, which means it is feasible to develop as an ecotourism destination. This is supported by the existence of the Maleo bird sanctuary, the potential for educational ecotourism, and the involvement of local communities. This research provides strategic recommendations for sustainable tourism development that is balanced between environmental conservation and improving the welfare of the surrounding community.